PADDY FARMING : POVERTY, REVENUE AND COST ANALYSIS - Thomson, Thomson (JALOW | Journal of Agribusiness and Local Wisdom, 2023)
To measure the level of feasibility of paddy farming in Lumbanjaean Village, Pahae North Tapanuli, North Sumatera, Indonesia in 2023 on 20 paddy farming selected by using snowballing sampling method, this study uses R/C analysis while to measure the poverty level of paddy farming, this study uses criteria for poverty levels equivalent to paddy consumption. Quantitatively, 3,53 will be the coeficient of R/C ratio means that, in Lumbanjaean Village, if a farmer spend the cost as much as IDR 1, then the farmer will receive income as much as IDR 3.53 thus the profit of this will be as much as IDR 2,53. Based on the criteria for poverty levels equivalent to paddy consumption, 316,9 kilograms of rice per person per year is classified as very poor to poor. Eventhough the R/C analysis stated that paddy farming in Lumbanjaean is feasible to be run, the poverty is still exist in this village. Increasing the level of education and skill is very suggested to be conducted by paddy farming in Lumbanjaean village, increasing price rice level by the governement, the importance of agricultare investment is needed to reduce porvety level in paddy farming in Lumbanjaean.